2023
DOI: 10.1002/pssr.202200509
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Local Dielectric Conductive Paths and Their Dynamics in the Degraded Multilayer Ceramic Capacitors

Abstract: Scanning thermal microscopy is used to perform direct imaging local conductive path and dynamic behaviors in the degraded multilayer ceramic capacitors (MLCCs) due to the thermal conductivity difference between the dielectric layers and the conductive regions. For local conductive path, its electrical tree dynamic growth behaviors under the dc bias on and off state are clearly obtained in the thermal image. Such phenomena reveal that space–charge‐limited current mechanism dominates in local conductive path reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…When considering the importance of efficient heat extraction for envisaged MLCC based EC coolers, thermal conductivity mapping of the electrocalorically active BaTiO 3 grains using the established 3ω SThM technique [27] would also be complementary to our SThM temperature mapping approach of EC heating. Previous studies have revealed that heterogeneity in thermal conductivity can be observed across different grains [28] as well as at grain boundaries [29], however such clear grain-related contrast is not evident in the BaTiO 3 MLCC studied by 3ω SThM by Du et al [30]. They do however identify locally enhanced thermal conductivity in pre-breakdown regions of degraded MLCC samples which may also be expected to give rise to a locally altered EC response.…”
Section: Resultsmentioning
confidence: 86%
“…When considering the importance of efficient heat extraction for envisaged MLCC based EC coolers, thermal conductivity mapping of the electrocalorically active BaTiO 3 grains using the established 3ω SThM technique [27] would also be complementary to our SThM temperature mapping approach of EC heating. Previous studies have revealed that heterogeneity in thermal conductivity can be observed across different grains [28] as well as at grain boundaries [29], however such clear grain-related contrast is not evident in the BaTiO 3 MLCC studied by 3ω SThM by Du et al [30]. They do however identify locally enhanced thermal conductivity in pre-breakdown regions of degraded MLCC samples which may also be expected to give rise to a locally altered EC response.…”
Section: Resultsmentioning
confidence: 86%